Role of Microperimetry in Observation and Treatment in Patients with Macular Holes - A. S. Zotov; A. S. Balalin; S. V. Balalin; A. M. Marukhnenko; T. G. Efremova (Oftalʹmologiâ)
Purpose: to assess the role of microperimetry in dynamic observation and treatment of patients with macular holes.Patients and Methods. Retrospective study of the microinvasive vitrectomy results using 25G or 27G technologies in 29 patients (29 eyes) with idiopathic macular holes (IMH). The examination included the determination of the best corrected visual acuity (BCVA), tonometry, perimetry, ultrasound biometry, optical coherence tomography, fundus photography, microperimetry.Results. After surgical treatment all patients have shown a significant improvement in BCVA and retinal photosensitivity (p < 0.05). A formula was derived for the dependence of BCVA after treatment on the initial retinal photosensitivity and the minimum IMH size, which can be applied to predict the results of surgical treatment.Conclusion. Microperimetry is a modern non-invasive examination method that allows with a higher density and resolution to localize central defects of the visual field and to carry out thorough monitoring before and after surgical treatment. The study of the retinal photosensitivity in the macular region and the minimum IMH size before treatment allow to predict BCVA in the postoperative period.